Penghapusan Kendaraan Dinas Rusak sebagai Solusi Mengurangi Biaya Pemeliharaan untuk Meningkatkan Efisiensi Pengelolaan BMD Pada Kantor BPKAD Kabupaten Sikka - Maria Oktaviranti; Andreas Rengga; Kristiana Reinaldis Aek (Jurnal Projemen UNIPA, 2026)
The management of Regional Government Assets is an imprortant aspect in supporting the effectiveness and efficiency of local government administration. One of the problems frequently faced by local governments is the high maintenance cost of official vehicles that are damaged or no longer fit for use, which leads to budget inefficiency and prevents effective asset management. This research used a qualitative research method, with data collection techniques consisting of interviews, observation, and documentation studies. The results of the research indicated that the disposal of damaged official vehicles was carried out through aucation and destruction mechanisms following the provisions of applicable laws and regulations. The disposal of official vehicles has been proven to reduce maintenance cost burdens and improve the efficiency of regional asset management. Therefore, the disposal of damaged offical vehicles constitutes a strategic solution for achieving efficient and accountable management of regional government assets.